2021
DOI: 10.1002/ange.202017249
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Coordination Toward a Photoinduced Single‐Chain Magnet Showing High Coercivity Values

Abstract: The production of photo‐switchable molecular nanomagnets with substantial coercivity, which is indispensable for information storage and process applications, is challenging. Introducing photo‐responsive spin‐crossover units provides a feasible means of controlling the magnetic anisotropy, interactions, and overall nanomagnet properties. Herein, we report a cyanide‐bridged chain 1⋅12H2O ({[(PzTp)FeIII(CN)3]2FeII(Pmat)2}n⋅12 H2O) generated by linking the FeII‐based spin‐crossover unit with the [(PzTp)Fe(CN)3]− … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…showing high coercivity values. 58 The results showed that the asymmetric coordination environment of the metal ion can effectively improve singleion magnetic anisotropy and enhance the global uniaxial anisotropy. In this respect, we decided to focus our attention on new cyanide-bridged {FeCo}-based assemblies by applying the asymmetric coordination strategy.…”
Section: Introductionmentioning
confidence: 97%
“…showing high coercivity values. 58 The results showed that the asymmetric coordination environment of the metal ion can effectively improve singleion magnetic anisotropy and enhance the global uniaxial anisotropy. In this respect, we decided to focus our attention on new cyanide-bridged {FeCo}-based assemblies by applying the asymmetric coordination strategy.…”
Section: Introductionmentioning
confidence: 97%
“…To date, one of the most widely studied photomagnetic effects is light-induced spin-state trapping (LIESST) in spin crossover (SCO) complexes, in which, for example, the spin states of Fe II ions can be switched between the low (S = 0) and high spin (S = 2) states by light irradiation. [15][16][17] However, most of these molecular systems, especially, photomagnets that exhibit light-induced magnetic ordering with hysteresis loops, 18,19 are operated at relatively lower temperatures. This is mainly because these photomagnets lack strong magnetic interactions and the photoexcited phase cannot survive at high temperatures.…”
Section: Introductionmentioning
confidence: 99%